(Dis)Assembling eSports: Material Actors and Relational Networks in the Chinese eSports Industry. Issue 5 (2nd November 2021) - Lin, Zhongxuan; Zhao, Yupei
ABSTRACT: Previous studies on eSports have essentially focused on its "sportiness" without giving attention to aspects such as media, information, and technology. By assessing the emerging research field of eSports through the lens of Actor-Network Theory, this study regards the Chinese eSports industry as an assemblage of heterogeneous elements. Accordingly, this study disassembles and unpacks eSports to understand how it is assembled, disassembled, and reassembled. Using research methods such as participant observation and in-depth interviews, this study evaluates the material actors and relational networks of the Chinese eSports industry to trace how the actors come to be assembled, how they associate and exercise force, and how they persist or decline each other's effects. Thus, it suggests that material actors and relational networks with an agency are not simply mediating, but also structuring eSports, indicating the explicit and implicit dynamics of power within the actor-network.